Prediction of Gastropathy Induced Non-Steroidal Anti-Inflammatory Agents in Patients with Rheumatoid Arthritis - Bobokulovna, Djabbarova Miyassar (American Journal of Bioscience and Clinical Integrity, 2025)
Objectives. To make an evaluation of the risk of the development of erosive and ulcerative lesions of the mucous membrane (MM) of the gastroduodenal zone induced by the intake of nonsteroid anti-inflammatory drugs (NSAIDs) on the basis of clinical and morphological parameters of the gastric mucosa in patients with rheumatoid arthritis (RA). The evaluation of predicting the risk of gastropathy development induced by the intake of NSAIDs (NSAID-gastropathy) with the application of discriminant analysis and multiple logistic regression was made in 74 patients (58 women and 16 men) with RA using the following clinical characteristics: age, the presence of complicated or uncomplicated gastroduodenal ulcer in their anamnesis, the intake of glucocorticoids, antiplatelet agents, duration of RA disease, gender, the presence of co-morbidities, the use of proton pump inhibitors, the duration of NSAIDs administration, simultaneous intake of two drugs from the group of NSAIDs, smoking, drinking alcohol in doses greater than the safe ones as well as the presence of dyspepsia symptoms. The assessment of the risk of NSAID-gastropathy development, based on clinical features and morphological parameters of ММ of the stomach (atrophy, inflammation, the activity of ММ, the amount of lymphoid follicles and the degree of the microorganism Helicobacter pylori contamination in the fundal and antral parts of the stomach was made in 33 patients (21 women and 12 men) with RA.